REPRESENTASI KEHIDUPAN MASYARAKAT PRASEJARAH PADA PERTUNJUKAN “A SONG FOR SANGIRAN 17” OLEH PREHISTORIC BODY THEATER - Soleh Sudarsono; Wahyu Novianto (PRASI, 2024)
This research issue focuses on the preservation of the cultural heritage of the Sangiran ancient human site. This research aims to analyse Preshistoricbody Theater in the performance titled A Song for Sangiran 17, as a representation of the life of prehistoric people. The research was conducted using a qualitative method. Qualitative methods are used to obtain factual data. The theory of Performance as Restoration by Richard Schechner is used as a scalpel in this research. Data was obtained using documentation studies and literature studies. The life narrative of prehistoric society becomes a reference in producing body language. The body is seen as a verbal language that produces ideas. The results of this research show that performance art is an effective medium to break the stereotypes that exist in society about cultural heritage sites that are often considered ancient and boring. By restoring the lives of prehistoric people, performing arts can represent cultural heritage sites well. These efforts are made as a form of preserving the cultural heritage of the Sangiran ancient human site. Performing arts thus becomes an effective bridge between the past and the present, creating an immersive and interactive experience that allows people to connect with prehistory. Keywords : Representation, prehistory, performing arts, preservation, Sangiran.   ABSTRAK Isu penelitian ini berfokus pada pelestarian cagar budaya situs manusia purba Sangiran. Penelitian ini bertujuan untuk menganalisis Preshistoricbody Theater dalam pertunjukan berjudul A Song for Sangiran 17, sebagai representasi kehidupan masyarakat prasejarah. Penelitian dilakukan menggunakan metode kualitatif. Metode kualitatif dipakai untuk mendapatkan data secara faktual. Teori Performance as Restoration oleh Richard Schechner dipakai sebagai pisau bedah dalam penelitian ini. Data didapatkan dengan menggunakan studi dokumentasi dan studi literatur. Narasi kehidupan masyarakat prasejarah menjadi acuan dalam memproduksi bahasa tubuh. Tubuh dipandang sebagai bahasa verbal yang memproduksi ide dan gagasan. Hasil penelitian ini menunjukkan bahwa seni pertunjukan menjadi media yang efektif untuk mematahkan stereotip yang ada di masyarakat tentang situs cagar budaya yang sering dianggap kuno dan membosankan. Dengan merestorasi kehidupan masyarakat prasejarah, seni pertunjukan dapat merepresentasikan situs cagar budaya dengan baik. Upaya-upaya ini dilakukan sebagai bentuk pelestarian cagar budaya situs manusia purba Sangiran. Dengan demikian seni pertunjukan menjadi jembatan yang efektif antara masa lalu dan masa kini, sehingga menciptakan sebuah pengalaman yang mendalam dan interaktif yang memungkinkan masyarakat terhubung dengan prasejarah.